INOVASI PENDIDIKAN EKONOMI DIGITAL UNTUK MENINGKATKAN LITERASI KEUANGAN GLOBAL - I Komang Satria Prima Jaya; Luh De Liska; Ni Luh Putu Cahayani (Arthaniti Studies, 2026)
This research discusses innovations in economic education in the digital and global era, focusing on enhancing financial literacy as a core competency. The background of this study is the urgent need to adapt the curriculum and teaching methods to the rapid development of digital technology and economic globalization. The aim of the study is to identify learning innovations and effective strategies that support the improvement of students' financial literacy. The research method is conducted through a systematic analysis of various relevant data sources that support the understanding and development of digital economic education. The analysis results show that the utilization of e-learning platforms, digital simulation-based learning, and the integration of fintech and digital entrepreneurship materials can significantly improve students' understanding of economic concepts and financial skills. Additionally, economic education that is adaptive to global changes equips students with international economic insights and the ability to compete in the global market. However, challenges such as unequal access to technology and the need for periodic curriculum updates must be addressed. In conclusion, innovations in digital economic education are a key factor in building strong financial literacy and addressing the dynamics of today's global economy